A Data-Driven Digital Framework for Enhancing Parental Engagement and Cognitive Development in Kazakhstani Children: A Survey and Correlation Study: Article - Aipenova, Aziza (Journal of Emerging Technologies and Computing, 2026)
This study examines early childhood cognitive development in Kazakhstan using a computational, technology-assisted method, highlighting the critical need for data-driven, culturally appropriate interventions. For statistical analysis, survey data from a cross-sectional sample of Kazakhstani parents (n=21) with children ages 0–6 were encoded. Correlation analysis showed a chronic implementation deficiency, although 93 % participants expressed strong awareness of early development. The study found a very strong negative relationship (r ≈ -0.88) between reported child anger/control issues (Variable N) and knowledge about significant brain development periods (Variable J), as shown in Table III. This suggests that parental education directly improves emotional management.On the other hand, a significant negative relationship (r ≈ -0.71) was found between reported speech clarity (Variable K) and brain knowledge (Variable J), showing that knowledgeable parents use stricter criteria when evaluating achievements. Furthermore, a strong positive correlation (r ≈ 0.638) has been found between the parents' subjective self-rating of the quality of early development (Variable E) and their technical knowledge of brain development (Variable J), indicating that more positive perceptions of developmental progress are related to a deeper understanding. Using the Vue and Vuetify frameworks, a prototype digital platform was created to fill these gaps and integrate awareness into consistent, evidence-based action. The study presents a scalable, data-driven approach for delivering culturally responsive early childhood interventions in the Kazakhstani context, despite its limitations due to its cross-sectional design and small sample size.